Nematodes as Important Source for Omega-3 Long-Chain Fatty Acids in the Soil Food Web and the Impact in Nutrition for Higher Trophic Levels - Menzel, Ralph; Geweiler, Diana; Sass, Annika; Simsek, Dilara; Ruess, Liliane (Frontiers in Ecology and Evolution, 2018)
PUFA (polyunsaturated fatty acids) content of food sources, in particular 3 long-chain PUFA with three or more double bonds, are considered essential for growth, reproduction, and neural development of higher animals. Surprisingly, and in contrast to aquatic ecosystems, 3 long-chain PUFA seem not widely available in terrestrial food webs. Far-reaching ideas indeed proclaim aquatic ecosystems as the principal source of these long-chain PUFA in the whole biosphere, including inhabitants of terrestrial ecosystems. Interestingly, de novo synthesis of 3 long-chain PUFA, which requires the presence of Δ12 (fat-2) and 3 (fat-1) desaturases absent in vertebrates, has been observed in nematodes, such as Caenorhabditis elegans. This raises the question if nematodes or other soil invertebrates present an important trophic link offering substantial supply in these valuable nutritional compounds in terrestrial food webs. This work followed the dietary routing of fatty acids of different C. elegans strains, including mutants defective in the PUFA biosynthesis, to two omnivorous Collembola species, Folsomia candida and Protaphorura fimata. The laboratory approach comprised microcosms offering binary links under various feeding conditions and analyzed growth, fecundity and dietary preference of consumers. Collembola did not prefer individual C. elegans strains as food source but they clearly reflected the PUFA-richness or -poorness of their nematode prey in their neutral lipid fraction. Moreover, Collembola did benefit from 3 long-chain PUFA rich diet, as shown by significant weight gain and increased number of laid eggs. Interestingly, the comparatively high PUFA-content of Collembola’s phospholipid fraction remained unchanged, even in response to almost PUFA-depleted nematode prey, suggesting that these Collembola species also possess the metabolic capability to de novo synthesize PUFA, including 3 long-chain forms. These findings broaden the basis of long-chain PUFA sources in terrestrial food webs and question the impact of aquatic ecosystems as principal source.